Approach to Chinese Address Forms from the Politeness Theory: The Case of The Dream of the Red Chamber - Yuanyi, Liu (Sinología hispánica. China Studies Review, 2026)
Politeness is fundamental in daily life and cross-cultural exchanges. The differences in politeness between China and Spanish-speaking countries are manifested in the forms of address. The lack of understanding of these differences by translators can lead to misunderstandings. This article, based on politeness theory, summarizes the pragmatic functions of Chinese address forms and, through a comparative analysis of the terms in The Dream of the Red Chamber and its translations, explores their main characteristics and pragmatic functions, with the aim of contributing to the dissemination and translation of Redology in the Spanish-speaking world.